Safety and effectiveness of double microcatheter technique in the treatment of ruptured aneurysms of anterior cerebral circulation - Zhao, Xintong; Zhang, Zihuan; Liu, Jiaqiang; Qin, Feiyun; Hu, Liying; Li, Zhenbao (Frontiers in Neurology, 2022)
Objective To evaluate the safety and effectiveness of the double microcatheter technique in the treatment of ruptured aneurysms of the anterior cerebral circulation. Methods Between 2012 and 2019, 113 patients with ruptured aneurysms of the anterior cerebral circulation were treated using the double microcatheter technique. Clinical records, angiographic results, and procedure-related complications were reviewed. Clinical and angiographic follow-up was performed. Results Complete occlusion, neck remnant, and partial occlusion were, respectively, recorded in 56.6, 38.9, and 4.4% of the total cases. For all patients, the incidence of intraoperative complications was 5.3% (6/113), and the overall rate of morbidity was 10.6% (12/113). Before discharge, three patients (2.7%) died. There was no procedure-related mortality. At discharge, favorable outcomes were observed in 79.6% (90/113) of the patients. High Hunt-Hess grades and receiving a craniotomy or external ventricular drainage were risk factors for clinical outcomes at discharge. Clinical follow-up was performed in 91 patients at a mean interval of 14.07 ± 11.68 months. At follow-up, favorable outcomes were observed in 92.3% (84/91) of the patients. Angiographic follow-up was performed in 66 patients at an average of 11.53 ± 11.13 months. The recurrence rate was 37.9%. Of these patients, 13 (19.7%) received retreatment. Conclusion The double microcatheter technique can be performed in ruptured aneurysms with high technical success and low morbidity/mortality. However, recurrence remains a problem, and patients should be followed up regularly.